Consensus Bundle on Postpartum Care Basics: From Birth to the Comprehensive Postpartum Visit. Issue 1 (January 2021) - Stuebe, Alison M.; Kendig, Susan; Suplee, Patricia D.; D'Oria, Robyn
Abstract : In the weeks after childbirth, a woman navigates multiple challenges. She must recover from birth, learn to care for herself and her newborn, and cope with fatigue and postpartum mood changes as well as chronic health conditions. Alongside these common morbidities, the number of maternal deaths in the United States continues to increase, and unacceptable racial inequities persist. One third of pregnancy-related deaths occur between 1 week and 1 year after delivery, with a growing proportion of these deaths due to cardiovascular disease; one fifth occur between 7 and 42 days postpartum. In addition, pregnancy-associated deaths due to self-harm or substance misuse are increasing at an alarming rate. Rising maternal mortality and morbidity rates, coupled with significant disparities in outcomes, highlight the need for tailored interventions to improve safety and well-being of families during the fourth trimester of pregnancy, which includes the period from birth to the comprehensive postpartum visit. Targeted support for growing families during this transition can improve health and well-being across generations. Abstract : The Postpartum Care Basics for Maternity Safety Bundle: From Birth to the Postpartum Visit presents strategies to improve maternal outcomes and standardize care.